Pharmacokinetic Evaluation of [C]CEP-32496 in Nude Mice Bearing BRAF Mutation-Induced Melanomas - Cuiping Jiang MMSc; Lin Xie MD, PhD; Yiding Zhang BSc; Masayuki Fujinaga PhD; Wakana Mori MSc; Yusuke Kurihara PhD; Tomoteru Yamasaki PhD; Feng Wang MD, PhD; Ming-Rong Zhang MD, PhD (Molecular Imaging)
CEP-32496, also known as RXDX-105 or Agerafenib, is a new orally active inhibitor for the mutated v-raf murine sarcoma viral oncogene homolog B1 (BRAF V600E ), which has attracted considerable attention in clinical trials for the treatment of human cancers. Here, we used carbon-11-labeled CEP-32496 ([ 11 C]CEP-32496) as a positron emission tomography (PET) radiotracer to evaluate its pharmacokinetic properties and explore its potential for in vivo imaging. Following radiotracer synthesis, we performed in vitro binding assays and autoradiography of [ 11 C]CEP-32496 in the A375 melanoma cell line and on tumor tissue sections from mice harboring the BRAF V600E mutation. These were followed by PET scans and biodistribution studies on nude mice bearing subcutaneous A375 cell-induced melanoma. [ 11 C]CEP-32496 showed high binding affinity for BRAF V600E -positive A375 melanoma cells and densely accumulated in the respective tissue sections; this could be blocked by the BRAF V600E selective antagonist sorafenib and by unlabeled CEP-32496. The PET and biodistribution results revealed that [ 11 C]CEP-32496 accumulated continuously but slowly into the tumor within a period of 0 to 60 minutes postinjection in A375-melanoma-bearing nude mice. Metabolite analysis showed high in vivo stability of [ 11 C]CEP-32496 in plasma. Our results indicate that [ 11 C]CEP-32496 has excellent specificity and affinity for the BRAF V600E mutation in vitro, while its noninvasive personalized diagnostic role needs to be studied further.